Implementasi Model Klarifikasi Nilai dalam Mengembangkan Kompetensi Meneladani Perilaku Masa Kanak-Kanak Nabi Muhammad SAW - Muhaimin Muhaimin (STAI Syaichona Moh. Cholil Bangkalan, 2015)
Abstract: This research is aimed at: (1) identifying the differences of students’ knowledge and attitudes towards following of the childhood behavior of Prophet Muhammad SAW between before and after the implementation of the values clarification model. The design of this research is quantitative research with a comparative approach one-group pretest-posttest design. The subjects were the students of class IV SDN Aengtabar 1 Bangkalan Regency. The data collection methods employed were a test to measure the knowledge and a questionnaire to measure the attitudes. The data were analyzed by using the statistical analysis paired samples t - test to compare the average score of the knowledge and attitudes / behaviors of the students. The overall students’ learning outcomes are better than before the implementation of this values clarification model. The implementation of this values clarification model effectively improved the students’ knowledge and attitudes to emulate the childhood behavior of Prophet Muhammad SAW. This values clarification model that was implemented to help the students understand the concepts being studied and develop a value system which is relied upon by the students make the consistent value choices